Angiotensin II Receptor Blockers but Not Angiotensin-Converting Enzyme Inhibitors Are Associated With a Reduced Risk of Acute Kidney Injury After Major Surgery - Yang, Shao-Yu; Huang, Tao-Min; Lai, Tai-Shuan; Chou, Nai-Kuan; Tsao, Chun-Hao; Huang, Yi-Ping; Lin, Shuei-Liong; Chen, Yung-Ming; Wu, Vin-Cent; NSARF study group, (Frontiers in Pharmacology, 2021)
Objective: We investigated the respective effects of preoperative angiotensin-converting-enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) on the incidence of postoperative acute kidney injury (AKI) and mortality. Methods: In this nested case-control study, we enrolled 20,276 patients who received major surgery. We collected their baseline demographic data, comorbidities and prescribed medication, the outcomes of postoperative AKI and mortality. AKI was defined by the criteria suggested by KDIGO (Kidney Disease: Improving Global Outcome). Logistic regression was used to assess the impact of exposure to ACEIs or ARBs. Results: Compared with patients without ACEI/ARB, patient who received ARBs had a significantly lower risk for postoperative AKI (adjusted odds ratio (OR) 0.82, p = 0.007). However, ACEI users had a higher risk for postoperative AKI than ARB users (OR 1.30, p = 0.027), whereas the risk for postoperative AKI was not significantly different between the ACEI users and patients without ACEI/ARB (OR 1.07, p = 0.49). Compared with patients without ACEI/ARB, both ACEI and ARB users were associated with a reduced risk of long-term all-cause mortality following surgery (OR 0.47, p = 0.002 and 0.60, p < 0.001 in ACEI and ARB users, respectively), without increasing the risk of hyperkalemia during the index hospitalization (p = 0.20). The risk of long-term all-cause mortality following surgery in ACEIs and ARBs users did not differ significantly (OR 0.74, p = 0.27). Furthermore, the higher the defined daily dose of ARB, the better the protection against AKI provided. Conclusion: Our study revealed that preoperative use of ARBs was associated with reduced postoperative AKI, which is better in high quantity, whereas preoperative use of ACEIs or ARBs were both associated with reduced mortality and did not increase the risk of hyperkalemia.